Perbandingan Gambaran Tuba Pada Pemeriksaan Hysterosalpingography (HSG) Dengan Klinis Infertilitas Primer di Rumah Sakit Siloam Sriwijaya Palembang: Studi Kasus - Lilis Rosalina; Mustika Fatimah; Muslimah Putri Utami; Rizka Muliani; Bunga Anggreini Sari (Jurnal Imejing Diagnostik (JImeD), 2024)
Background: In dealing with infertility problems, a deep understanding of the specific causes becomes very important for proper treatment. One of the diagnostic methods often used to assess infertility conditions is hysterosalpingography (HSG). The superiority of HSG lies in its ability to provide clear visual information about the structural condition of the uterus and fallopian tubes, which are key factors in fertilization.Methods: This qualitative descriptive research uses a case study approach conducted at Sriwijaya Siloam Hospital in Palembang to compare the results of HSG examination in primary infertility clinics.Results: In this study, the results of HSG examinations in two patients with clinical primary infertility showed that there was a difference in the picture. The results of the HSG examination in first patient showed both non-patent tubes, where distal occlusion of the right fallopian tube and left peritubal adhesion were found, while in second patient it showed both patent tubes with a positive spill sign.Conclusions: Differences in the results of HSG examinations in primary infertility clinics show the conclusion that even though HSG shows a patent fallopian tube, the couple may still experience primary infertility. This shows that the cause of infertility can come from other factors and requires further evaluation.